Peningkatan Produktivitas Menggunakan The American Productivity Center (APC) Pada PT Arta Boga Cemerlang Palembang - Meylinda Mulyati (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
PT Arta Boga Cemerlang is the sole distributor that distributes products from a number of manufacturers throughout Indonesia. In the face of competition among businesses in this era of globalization, a company must be supported by strategy and tactics in doing business actions. To determine the level of productivity PT Arta Boga Cemerlang, it is necessary to measure productivity. Productivity measurement performed using The American Productivity Center (APC) model. Model APC also can perform measurements of profitability and improvement price index. The data required for productivity analysis is taken from the year 2012 as the base period until 2015. The results of analysis of productivity measures that have been done show that the level of productivity PT Arta Boga Cemerlang in 2015 increased by 3,010%.